The analysis of partisan differences in advanced democracies: the “independent variable problem” reconsidered - Zohlnhöfer, Reimut (Zeitschrift für vergleichende Politikwissenschaft, 2023)
The paper challenges the idea that using governing parties’ policy positions is necessarily desirable in quantitative analyses of partisan differences in public policies. Rather, for some research questions parties’ affiliation with certain party families is the preferable solution. The paper shows that the use of policy positions instead of party family affiliation shifts the research question from asking whether parties make a difference in public policy to the question whether parties in government do what they promise. This shift can have considerable analytical costs and can potentially blindfold scholars for certain dynamics. Moreover, the use of party family affiliation has less drawbacks than is often claimed even under multidimensional party competition if the simple distinction between left, center and right parties is abandoned and more fine-grained data for various party families are used.
Gesehen am 01.08.2024